Gender differences in the perception of subjective vs. objective cognitive decline: Baseline data from the SCD‐Well Trial: Examining subjective cognitive decline in diverse, ethnoracial populations. (7th December 2020) - Meiberth, Dix U.; Schild, Ann‐Katrin; Sannemann, Lena; Müller, Theresa; Demnitz‐King, Harriet; Whitfield, Tim; Schlosser, Marco; Krolak Salmon, Pierre; Molinuevo, Jose Luis; Klimecki, Olga; Wirth, Miranka; Chetelat, Gael; et al.
Abstract: Background: Subjectively experienced cognitive decline (SCD), particularly associated with worries, in older adults is known to be a risk factor for dementia. So far, only few studies focus on gender‐specific profiles in SCD. Method: Gender differences in SCD subjects who were enrolled in the SCD‐Well trial were analyzed with regard to their perception of subjective cognitive difficulties and the corresponding objective cognitive performance. SCD‐Well is a multicenter, observer‐blinded, randomized, and controlled superiority trial (Marchant et al. 2018). Two different types of 8‐week interventions are compared within the study: a mindfulness‐ and compassion‐based intervention with a validated health education program. 147 participants (95 female) were included. Data from the SCD‐Interview (SCD‐I; Miebach et al., 2019), the Cognitive Difficulties Scale (CDS; McNair & Kahn, 1983), and different cognitive scales summarized in a modified Preclinical Alzheimer's Cognitive Composite (PACC; Donohue et al., 2014) were analyzed for gender differences. Result: Statistical analyses revealed no gender differences concerning variables of the SCD‐I and CDS. Regarding objective cognitive performance, a significant gender effect for the PACC score with men showing lower cognitive performance was detected (U = 1859.00, p < .05). However, only women showed a negative correlation between the PACC and reported SCD as indicated on the SCD‐I (r=‐.436, p= < .001) and CDS (r = ‐.514, p < .001): more subjective cognitive difficulties and worries were associated with lower cognitive performance. To further explore this relationship, we will analyse differences between sites. Conclusion: Literature reveals gender differences in SCD for objective cognition, neuroimaging and biomarkers (Wang & Tian, 2018). The present study supports the finding of woman performing better in a cognitive assessment than men. Moreover, it adds to this literature by showing an association between self‐perceived cognitive difficulties and actual cognitive performance in women, but not men. Further research is needed to provide a deeper understanding of gender differences in SCD, which are highly relevant for approaches on early detection of cognitive decline, which might in turn impact the choice of pre‐clinical interventions.